Prehending Addiction: Alcohol and Other Drug Professionalsâ€™ Encounters With â€œNewâ€? Addictions - Farrugia, A.; Fraser, Suzanne (Sage Publications, 2017)
© 2017, © The Author(s) 2017. This article investigates the ways new forms of addiction are encountered by professionals working in the area of alcohol and other drugs. Combining interviews with policymakers, service providers, and peer advocates in three countries (Australia, Canada, and Sweden), and Mike Michael’s utilization of the notion of prehension for science communication, we track the notions of addiction, drugs, and subjectivity that emerge when alcohol and other drug professionals encounter what Fraser, Moore and Keane call the addicting of nonsubstance-related practices. The analysis has three parts: constituting addiction unity, questioning addiction unity, and conflicting logics of addicting processes. We argue that specific articulations of drugs and health and specific health professional and addiction subjects are made anew in these encounters. These notions of drugs, health, and subjectivity shape how alcohol and other drug professionals engage with substance-related addictions. In concluding, we consider the implications of new addictions for professional practice.